Sessualità normate tra pratiche educative e voci adolescenti. Un’esperienza etnografica nei consultori di Roma - Manfroni, Alice (Antropologia Pubblica, 2024)
This paper aims to reflect on the interconnection between sexuality, gender and age. Moving from my ethnographic research conducted in Rome concerning the sexual education activities carried out in schools by some public family counseling, I discuss the sexuality of adolescents and its meanings within a specific health and social institution through a critical analysis of the discursive categories used by the social actors met in the field. The anthropological gaze gives back legitimacy to the plurality of roles, subjectivities, sexual and affective relationships that teenagers experience in their everyday lives. The analysis will show how anthropology can restore the complexity of legal and socio-cultural norms, by answering to the adolescents’ needs, and by building sexual education activities starting from the teenagers’ voices and experiences. Finally, I will attempt to bring out the capacities of feminist anthropology both of problematizing normative discourses and proposing an alternative discourse regarding sexuality, relationship, and adolescence.